An Example of A Manuscript Poetic Tajweed Treatise (Transcription and Edition of the Critical Study) - Alemdar, Yusuf (Scholarya Demo Journal of Ruby, 2021)
This article is an edition of the critical study that includes transcription, translation, development with footnotes and finally evaluation on a concise, poetic manuscript named as Qavaid al-Qur’an and Tajveed al-Calam al-Elahi, written by a person named Husam b. (ben: son of) Khalifah al-Marashi, whose identity and personality could not be determined. Consisting of 60 couplets, this work looks like a very small treatise that fit on the front/single page of a leaf. Dealing with the subjects in two parts, the author explains the origins of the letters in the first part; in the second part, which he divided into ten parts, he expressed some basic issues regarding the recitation of the Qur'an according to Hafs narration of Qiraah Asim in poetic form. The author, also and probably later added some verses about some recitation rules that he put forward in a terse manner, in the margins of the work -in the form of annotationswhose examples have been shown by us with scientific methods.